Factors Affecting the Innovative Behavior of Government Employees - Ulung Pribadi; Muhammad Iqbal; Monika Siti Aisyah (Journal of Local Government Issues (LOGOS), 2022)
This study examined organizational structure, culture, leadership, satisfaction, and Information and Communication Technology (ICT) adoption to predict employee innovation. This study used a survey data collection method and a purposive sampling technique of respondents who did innovative behavior in realizing good governance and providing public services. The questions were created using a Likert scale. Structural Equation Model-Partial Least Square (SEM-PLS) examined the data to determine its validity and reliability and test hypotheses and regression. This study found that organizational structure, culture, and leadership positively and significantly influenced employees’ satisfaction, with p-values of 0.000, 0.000, and 0.010, respectively. Moreover, employees’ satisfaction and ICT adoption also positively and significantly influenced employees’ innovation. Organizational structure, organizational culture, and leadership had a substantial impact on employees' satisfaction (R-square = 0.865), and employees’ satisfaction and ICT adoption substantially impacted employees' innovation (R-square = 0.887). The limitations and implications of this study are evaluated.